Strategic role of mobile commerce (M-Commerce) payment system: Establishing new competitive advantage - Abdullah, Haim Hilman; Bohari, Abdul Manaf; Warokka, Ari; Abdussalam, Ashraf (IBIMA Publishing, 2012)
A Mobile based payment system or m-commerce is an emerging issue of e-commerce in Malaysia.It is recognized by both academia and practitioners as one of the fastest growing and preferable medium of making business transactions.This study investigated the benefits of m-commerce payment method, and services satisfaction on m-commerce providers. Respondents were those who had experienced using this mode of payment.The main objectives of the study were; a) to determine the level of m-commerce awareness in Malaysia; b) to determine the level of m-commerce payment system usage among Malaysian; c) to determine the level of m-commerce payment environment among Malaysian; and d) to determine the relationship between payment system and payment environment toward m-commerce services satisfaction.The results show that m-commerce is another tool that is both highly intangible and possesses specific characteristics.It can be developed and made as another avenue for firms to create competitive advantage.